The ergonomics planning of the electronic educational modules in the conditions of the open module multimedia system (Journal of Information Technologies in Education (ITE), 2009)
The actuality task of choice of the electronic educational module is considered in work. The method of choice, allowing to take into account different requirements and preferences taught on each of criteria of choice, and algorithm of realization of this method, is developed. Offered approach allowed not only to get quantitative estimations for each of alternatives and to choose the best but also check up the rightness of estimation.
Keywords: analytic hierarchy process; e-learning; electronic educational module